FINANCING COMPARISON OF UMKM CONVENTIONAL BANKS AND SYARIAH BANKS IN INDONESIA - ela elliyana; irmah halimah Bachtiar (Universitas Trisakti, 2020)
The purpose of this study was to compare the increase in lending for Micro, Small and Medium Enterprises (UMKM) by Islamic banks and conventional banks after determining the minimum percentage of UMKM credit distribution from the total ceiling of commercial bank lending through Bank Indonesia Regulation (PBI) Number 17/12 /PBI/ 2015, where the mandatory amount of commercial bank lending applies gradually at 5% in 2015 to 20% in 2018. Using quantitative data sourced from the Financial Services Authority (OJK) using the parametric inferential statistical method with the independent T-Test technique, in two homogeneous groups that have no relationship, namely the Islamic bank group and the conventional bank group. The result is that the average increase in the amount of UMKM lending in Islamic banking is greater than that of conventional banks.